Młodzi, wykształceni, z miasta. . . - o wsparciu społecznym internautów = Young, educated, from the city. . . - about social support of Internet users - Jeran, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Young and educated inhabitants of cities constitute - alongside so called net-generation - the category of the most digitally enabled Poles. The presented research focused entirely on them so as to allow referring to deeper determinants of digital inclusion than the division into users and non-users of the Internet. The study was performed in 2012 as a questionnaire interview on 400 Internet users - inhabitants of cities of the Kuyavian-Pomeranian region aged 18-34, with at least secondary education.
Keywords: social capital; Internet users; net generation; kapitał społeczny; użytkownicy internetu; pokolenie sieci